'New professionalism' of the teacher and education towards interculturalism. (2015) - Ogrodzka-Mazur, Ewa; Gajdzica, Anna
In the undertaken considerations, which explore the issues of preparing teachers for intercultural education, theoretical conceptualisation, referring to Julian Elliot's concept of 'new professionalism', has been applied. Its essence consists in a reflective approach and examining teachers' own practice. The conducted analyses and interpretations allowed for outlining real professional preparation of teachers in the context of needs, tasks and demands of intercultural education. In accordance with Elliot's model of teacher's professional practice, four elements were taken into account in the outline: the context, properties of the professional role, and the character of both professional competence and professional knowledge.